A noninvasive eDNA tool for detecting sea lamprey larvae in river sediments: Analytical validation and field testing in a low‐abundance ecosystem. Issue 6 (19th April 2022) - Baltazar‐Soares, Miguel; Pinder, Adrian C.; Harrison, Andrew J.; Oliver, Will; Picken, Jessica; Britton, J. Robert; Andreou, Demetra
Abstract: Anthropogenic activities are increasingly threatening aquatic biodiversity, especially anadromous species. Monitoring and conservation measures are thus required to protect, maintain and restore imperilled populations. While many species can be surveyed using traditional capture and visual census techniques, species that use riverine habitats in a less conspicuous manner, such as sea lamprey Petromyzon marinus, can be more challenging to monitor. Sea lamprey larvae (ammocoetes) can spend several years in freshwater burrowed within soft sediments, inhibiting their detection and assessment. Here, we present a qPCR assay based on the detection of environmental DNA (eDNA) to identify the presence of ammocoetes burrowed in the sediment. We present an extensively validated method that ensured both species‐specificity of the assay as well as the capacity to detect ammocoetes when abundances are low. Experiments on burrowing activity suggested that most of the DNA released into the sediment occurs during burrowing. Overall, we demonstrate this new molecular‐based tool is an efficient and effective complement to traditional monitoring activities targeting larval stages of sea lampreys.